Un-English Accentual Patterns of the Interlanguage Prosody of Students Reading for a Master’s Degree in Applied Language Studies, University of Constantine: Underlying Causes and Remedial Didactic Practices - DJALAL, Mansour (Journal of Human Sciences, 2017)
The author of the present research paper digitally recorded the renderings of 260 monomorphemic and affix words of different accentual patterns and moraic structures along with ten utterances performed by thirty two MA English majors at the Department of Letters and English Language, Constantine University 1. This paper reports on the inferred causes underlying the diagnosed stress-allocation errors, and remedial didactic insights are sketched out. The findings reveal that the respondents have not accommodated their interlanguage phonology to L2 parameters due to a number of interlocked factors: (1) lack of internalised rules regarding stress correlates and stress-assignment guidelines; (2) non-strategic and infrequent usage of print and electronic dictionaries; (3) failure to take advantage of the copious merits of Computer Assisted Pronunciation Learning and (4) shallow pronunciation-promoting strategies.